Compatibility of entomopathogenic nematodes and aqueous plant extracts aiming at the control of fruit fly Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) - Rohde, Cristhiane; Moino Junior, Alcides; Krupa, Patrícia; Ramalho, Kaio Roger de Oliveira (Semina: Ciências Agrárias, 2013)
Currently, the fruit fly Ceratitis capitata (Diptera: Tephritidae) has been controlled mainly by the chemical method, which is responsible for environmental and public health impacts. It has often been ineffective due to development of resistant insect populations. Thus, it has necessary to research new effective and less impacting control forms. In this sense, the use of entomopathogenic nematodes and plant extracts has been effective for controlling this pest. However, studies are needed to assess the compatibility between these methods, aiming at their use in integrated management programs for this pest. The aim of this study was to evaluate the compatibility of the nematodes Steinernema carpocapsae ALL and Heterorhabditis sp. JPM4 with aqueous extracts prepared from dried plant of cinnamon leaf, twig and fruit (Melia azedarach), rue leaf (Ruta graveolens), ginger (Zingiber officinale) and garlic (Allium sativum) for the control of C. capitata. The bioassay was carried out in completely randomized design with four replicates per treatment. Each replication consisted of a glass tube containing 1 mL of plant extract 40% w/v and 1 mL suspension of entomopathogenic nematodes with 1800 JI/mL for S. carpocapsae ALL and 600 JI/mL for Heterorhabditis sp. JPM4. The viability and infectivity of this nematode were evaluated on C. capitata larvae after 48 and 120 hours. It was found that all extracts reduced the viability and infectivity of both nematodes and they were incompatible after 120 hours of exposure. The nematode Heterorhabditis sp. JPM4 was more sensitive than the S. carpocapsae ALL as it showed, in the first 48 hours, a reduction in the viability and infectivity of more than 80 and 75%, respectively, when exposed to all the extracts except the ginger.